Characterization, therapeutic applications, structures, and futures aspects of marine bioactive peptides - Ashraf, Azqa; Ud Din, Aiman Salah; Hussain, Mudassar; Khan, Imad; Hassan, Farazia; Ahmad, Adnan; AL-Ansi, Waleed; Lou, Zaixiang (International Journal of Environment, Agriculture and Biotechnology, 2023)
Bioactive peptides from marine species have gained attention due to their promising biological features, and the disciplines of pharmaceutical, cosmeceutical, nutraceutical, and biomedical product development have increased recently. Their molecular mass, immunity, and natural abilities that they evolved are essential for host defense mechanisms. Marine bioactive peptides have extremely complex and diverse structures that vary greatly depending on the sources from which they are obtained. They frequently have secondary structures and can be cyclic in the form of depsi-peptides. Bioactive peptide purification from marine sources can be achieved via chromatography techniques, including reverse-phase high-performance liquid chromatography, gel filtration chromatography, and ion exchange chromatography, which is a current technique to extract biologically active peptides. Studies of marine plants, microbes, and animals over the last several eras have revealed a huge variety of structurally varied and bioactive secondary metabolites. With a particular focus on the conversion of nutraceutical and pharmaceutical research into commercially available products, this review summarizes current findings in marine peptide research as well as emerging patterns, and its promising directions are briefly reviewed. The use of active peptides derived from the sources mentioned earlier their health advantages and bioactivities are also focused. Along with safety concerns, their possible usages in the processed food industry, wound healing, feed, cosmetic, and pharmaceutical industries, for the growth of efficient goods, are highlighted.